If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + y)(5y + -7) = 0 Reorder the terms: (8 + y)(-7 + 5y) = 0 Multiply (8 + y) * (-7 + 5y) (8(-7 + 5y) + y(-7 + 5y)) = 0 ((-7 * 8 + 5y * 8) + y(-7 + 5y)) = 0 ((-56 + 40y) + y(-7 + 5y)) = 0 (-56 + 40y + (-7 * y + 5y * y)) = 0 (-56 + 40y + (-7y + 5y2)) = 0 Combine like terms: 40y + -7y = 33y (-56 + 33y + 5y2) = 0 Solving -56 + 33y + 5y2 = 0 Solving for variable 'y'. Factor a trinomial. (-8 + -1y)(7 + -5y) = 0Subproblem 1
Set the factor '(-8 + -1y)' equal to zero and attempt to solve: Simplifying -8 + -1y = 0 Solving -8 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1y = 0 + 8 -1y = 0 + 8 Combine like terms: 0 + 8 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8Subproblem 2
Set the factor '(7 + -5y)' equal to zero and attempt to solve: Simplifying 7 + -5y = 0 Solving 7 + -5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5y = 0 + -7 -5y = 0 + -7 Combine like terms: 0 + -7 = -7 -5y = -7 Divide each side by '-5'. y = 1.4 Simplifying y = 1.4Solution
y = {-8, 1.4}
| -4x-1-3x=48 | | 4y=-3x+5 | | -4/7x=-49.23 | | -4z(z-9)(z+1)=0 | | 6(13-5)+45=62 | | (8+y)(5y+8)=0 | | s(t)=-90t+720 | | 3X-12=-57 | | -4z^2+36=0 | | z^2+2z=74 | | 50/(r-2.5)+50/(r+2.5) | | y=7/9*0.7778-7 | | x+(-19sqrt(x))+60=0 | | 4742*x=2371 | | -4(t-5)+6t=5t-9 | | x+(x+2)+(x+4)+(x+6)=212 | | 9m=18+3m | | x+2+4x=-3 | | x=6x+4 | | x-19*sqrt(x)+60=0 | | y=7/9(-7)-7 | | 100r=40(r^2-6.25) | | -7x+36=15 | | 100r=40r(r^2+2.5) | | 0.1+2x^2=0 | | -5x+8-3x=-88 | | 8(3x-12)=88x | | 3/7x-1/6x | | -6(8+x)=18 | | -x(2x-3)=527 | | x+3.6=8 | | 5x+10(-1)=-15 |